2012
DOI: 10.5194/bg-9-1633-2012
|View full text |Cite
|
Sign up to set email alerts
|

The nitrogen isotope effect of benthic remineralization-nitrification-denitrification coupling in an estuarine environment

Abstract: The nitrogen (N) stable isotopic composition of pore water nitrate and total dissolved N (TDN) was measured in sediments of the St. Lawrence Estuary and the Gulf of St. Lawrence. The study area is characterized by gradients in organic matter reactivity, bottom water oxygen concentrations, as well as benthic respiration rates. N isotope effects on the water column associated with the benthic exchange of nitrate (&epsilon;<sub>app</sub>) and TDN (&epsilon;<sub>sed</sub>) during be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 37 publications
8
52
1
Order By: Relevance
“…Our experiments show that increasing this factor from 0 to 4 ‰ requires almost triple the BD rate needed to maintain the global mean δ 15 NO 3 at observed levels. Recent estimates suggest that the net fractionation factor may be even higher (4-8 ‰) due to fractionation within the nitrification-denitrification loop in the sediments (Granger et al, 2011;Alkhatib et al, 2012). If these high-end estimates are validated on a global scale, this could require larger BD : WCD ratios than our largest value simulated here (> 3.5).…”
Section: Discussioncontrasting
confidence: 38%
See 3 more Smart Citations
“…Our experiments show that increasing this factor from 0 to 4 ‰ requires almost triple the BD rate needed to maintain the global mean δ 15 NO 3 at observed levels. Recent estimates suggest that the net fractionation factor may be even higher (4-8 ‰) due to fractionation within the nitrification-denitrification loop in the sediments (Granger et al, 2011;Alkhatib et al, 2012). If these high-end estimates are validated on a global scale, this could require larger BD : WCD ratios than our largest value simulated here (> 3.5).…”
Section: Discussioncontrasting
confidence: 38%
“…Recent studies (Lehmann et al, 2007;Granger et al, 2011;Alkhatib et al, 2012) have suggested a higher net fractionation factor associated with BD (ε BD = 4-8 ‰) compared to previous estimates (ε BD = 1-3 ‰) (Brandes and Devol, 2002;Lehmann et al, 2004). They suggest BD should have a much higher net fractionation factor due to the measured high δ 15 NH + 4 that is presumably released from the sediments where BD occurs.…”
Section: Isotope Effect Of Benthic Denitrificationmentioning
confidence: 42%
See 2 more Smart Citations
“…In sediments, the reaction rate is limited by diffusion, and, accordingly, this fractionation effect is not visible in the apparent fractionation during sedimentary denitrification (e.g., Brandes and Devol, 2002). Recent studies (Lehmann et al, 2007;Alkhatib et al, 2012) propose that the intrinsic isotope effect of denitrification in sediments is comparable to that of water column denitrification.…”
Section: The Nature and Isotope Effect Of Nitrate Reductionmentioning
confidence: 99%